Semiotic Analysis of Ferdinand De Saussure's Structuralism in the Short Film Cindhe by Gesy Lutfiah R.O - Anisatullatif, Mashitoh (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
This research presents a short film entitled "Cindhe" based on the sign system in the discipline of Structural Semiotics. This research discusses the sign aspect using Ferdinand de Saussure's theory. In the important minutes of the scene, an analysis of this short film work will be presented based on the signs of Structuralism Semiotics. Based on the analysis, simultaneously with the interpretation of the aspects and each scene analyzed. This research uses the structuralism semiotics analysis method by correlating several signs in it, so that it can show a picture that has a meaning of everyday life that has a good impact in the future if taken on the positive side.